2018
DOI: 10.1289/ehp3802
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mouse Model of Experimentally Induced Endometriosis to Evaluate and Compare the Effects of Bisphenol A and Bisphenol AF Exposure

Abstract: Background: Endometriosis is a gynecological disease affecting 1 in 10 women of reproductive age. Endometriosis incidence has risen; however, whether this rise is due to disease awareness or environmental contamination is not known. Objective: The objective of this study was to determine if bisphenol A (BPA) or bisphenol AF (BPAF) potentiate the development of endometriosis and if hormonal status alters how toxicant exposure affects disease. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 67 publications
3
46
0
Order By: Relevance
“…Minced uterine tissue was injected into the peritoneal cavity of host mice. In this study, BPA treatment disrupted ovarian steroidogenic pathways resulting in lower progesterone levels and higher atretic oocyte numbers [60]. BPAF and BPA had higher epithelial proliferation scores, although this was only significant in the highest dose of 900 ppm.…”
Section: Summary Of Exposures and Outcomes In Epidemiological Studiesmentioning
confidence: 60%
See 2 more Smart Citations
“…Minced uterine tissue was injected into the peritoneal cavity of host mice. In this study, BPA treatment disrupted ovarian steroidogenic pathways resulting in lower progesterone levels and higher atretic oocyte numbers [60]. BPAF and BPA had higher epithelial proliferation scores, although this was only significant in the highest dose of 900 ppm.…”
Section: Summary Of Exposures and Outcomes In Epidemiological Studiesmentioning
confidence: 60%
“…BPAF and BPA had higher epithelial proliferation scores, although this was only significant in the highest dose of 900 ppm. Both compounds mimicked estrogen, with BPAF having a stronger effect than estrogen [60]. Taken together, these data suggest that BPA and related compounds can affect mechanisms important in the pathophysiology of endometriosis.…”
Section: Summary Of Exposures and Outcomes In Epidemiological Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Specifically, BPA exposure has been associated with polycystic ovary syndrome [30], ovarian insufficiency [31], and infertility [32]. In regard to endometriosis, an in vivo study reported changes in endometrial lesions after exposure to BPA or its analogues [33], although a recent meta-analysis revealed only limited and contradictory epidemiological evidence on the association between BPA exposure and endometriosis risk [34]. By contrast, there has been no published research on the association between exposure to BPS or BPF and endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among those, we choose to focus our study on emerging bisphenols: Bisphenol A Diglycidyl Ether (BADGE) and Bisphenol AF (BPAF) because very little data exists on their effects on mammalian germ cells. However, recent studies have shown that, as BPA, BPAF induces the release of ROS in adult oocytes, delaying in vitro maturation (Ding et al, 2017;Jones et al, 2018).…”
Section: Introductionmentioning
confidence: 99%